2020
DOI: 10.1145/3415142
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Gaming as a Tool for Subjectivizing Visitor Experience at Cultural Heritage Locations—Case Lights On!

Abstract: This article discusses an augmented reality game as a way of subjectivizing visitor experience at cultural heritage locations. The text describes the starting point, development aims, and some initial user data of the Lights On! game while contextualizing the game's development with relevant discussion concerning the use of ludic and narrative augmented reality elements in enhancing the experience of place at historical sites. The initial user data were collected via an in-app questionnaire and learning diarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Engagement is a feature that visitor-location-based AR game interactions share with other HCI environments, and the application of games is a key component in shaping visitor experience and behavior. As a positive technology that subjectivizes visitor experience, AR games at cultural heritage sites can induce satisfaction and pleasure [59], and participation comes from this positive experience [60]. In studies investigating the impact on user engagement and experience, it was found that controlbased games, performing a character's physical tasks, or customizing a character's behavior enhances the fun and positively affects engagement [61].…”
Section: Location-based Ar Games and Cultural Heritage Tourism Experi...mentioning
confidence: 99%
“…Engagement is a feature that visitor-location-based AR game interactions share with other HCI environments, and the application of games is a key component in shaping visitor experience and behavior. As a positive technology that subjectivizes visitor experience, AR games at cultural heritage sites can induce satisfaction and pleasure [59], and participation comes from this positive experience [60]. In studies investigating the impact on user engagement and experience, it was found that controlbased games, performing a character's physical tasks, or customizing a character's behavior enhances the fun and positively affects engagement [61].…”
Section: Location-based Ar Games and Cultural Heritage Tourism Experi...mentioning
confidence: 99%
“…Such an approach adds new dimensions to the user experience where gamification is just one step away. Indeed, a somewhat recent work addresses this dimension via subjunctivization of visitors' experience at cultural heritage locations [35]. This subjunctivization is about gamification approach using augmented reality.…”
Section: New Solutions For Blockchain Based Cultural Heritage Preserv...mentioning
confidence: 99%
“…Thus, they increased users' feeling of connectedness to the place through shared social experiences. Prior work by Kostopoulou et al [53] and Lehto et al [61] used locationbased AR to revive historical places and visitors' understanding and attachment to them. Both emphasized the importance of spatially embedded cues and the user experience onsite.…”
Section: Meaning and Sense Of Placesmentioning
confidence: 99%